Technology readiness and implications for higher education in Universities in North-Central Nigeria - Jumoke Iyabode Oladele (Interdisciplinary Journal of Education Research)
The fourth industrial revolution emphasises classroom innovation with digital and smart technology. It examined students' preparation for technology-driven education in higher education and the fourth industrial revolution. A descriptive survey research design was adopted for this study. The population consisted of students from tertiary institutions, while the target population included university undergraduate and postgraduate students in universities in North-Central Nigeria. The sample comprised five hundred and seventy students across three types of institutions in Nigeria (i.e. private, state, and federal-owned institutions), drawn using proportionate and cluster sampling techniques. Data were collected using a researcher-designed and validated questionnaire with an overall reliability index of 0.86. The collected data were analysed descriptively, and non-parametric inferential statistics were tested at a 0.05 level of significance. Students were ready to use educational apps for studying, engage with immersive tech tools while learning, learn about IoT as part of their learning trajectories for 4IR compliance, embrace many technological innovations while learning, and engage in lifelong learning. Moderately technology-ready students had significant gender, age, institution, and degree of study demographics. Also, given the contemporary 4IR reality, pupils were somewhat ready for technology-enhanced education and positively inclined toward technology-driven abilities. Group dynamics are crucial to preparation. Therefore, it is recommended that students be given the opportunity to improve their technical abilities to prepare them for meaningful teaching and learning. This can be done by investing in technology, training students, and passing regulations that support worldwide competitive online learning.